BARRIER-ORIENTED SKIN CARE DURING TOPICAL ACNE THERAPY: A NARRATIVE REVIEW FOR ESTHETICIANS - Anzhelika Syveniuk (Program Studi Pendidikan Tata Rias, 2026)
Acne remains one of the most common chronic inflammatory skin conditions, and standard treatment protocols — retinoids, benzoyl peroxide, and acid-based exfoliants — have traditionally focused on suppressing inflammation and seborrhea, often overlooking the condition of the skin barrier. Emerging evidence indicates that barrier dysfunction is not merely a side effect of therapy but an active contributor to acne pathophysiology. Altered epidermal lipid composition and elevated transepidermal water loss (TEWL) have been reported in acne-prone skin before treatment begins. Barrier impairment during aggressive acne therapy further contributes to post-inflammatory complications, including hyperpigmentation, erythema, chronic reactivity, and reduced treatment adherence. This narrative review synthesizes current peer-reviewed evidence on the relationship between barrier dysfunction and acne course, drawing on clinical trials, systematic reviews, and mechanistic studies published primarily within the last decade. The review examines how conventional topical agents disrupt barrier integrity, evaluates the clinical evidence for barrier-supportive adjuncts such as ceramide-containing moisturizers and pH-balanced cleansers, and summarizes practical strategies for estheticians and skin care professionals working at the intersection of cosmetology and dermatology. Findings suggest that incorporating barrier-support measures alongside standard acne therapy can reduce irritation and improve adherence without compromising therapeutic efficacy. Based on this evidence base, the review also introduces a practical, barrier-oriented framework for non-physician skin care professionals supporting clients undergoing active acne treatment.